MicroRNAs in pancreatic cancer drug resistance: mechanisms and therapeutic potential - Dong, Fangying; Zhou, Jing; Wu, Yijie; Gao, Zhaofeng; Li, Weiwei; Song, Zhengwei (Frontiers in Cell and Developmental Biology, 2025)
Pancreatic cancer (PC) remains one of the most lethal malignancies, primarily due to its intrinsic resistance to conventional therapies. MicroRNAs (miRNAs), key regulators of gene expression, have been identified as crucial modulators of drug resistance mechanisms in this cancer type. This review synthesizes recent advancements in our understanding of how miRNAs influence treatment efficacy in PC. We have thoroughly summarized and discussed the complex role of miRNA in mediating drug resistance in PC treatment. By highlighting specific miRNAs that are implicated in drug resistance pathways, we provide insights into their functional mechanisms and interactions with key molecular targets. We also explore the potential of miRNA-based strategies as novel therapeutic approaches and diagnostic tools to overcome resistance and improve patient outcomes. Despite promising developments, challenges such as specificity, stability, and effective delivery of miRNA-based therapeutics remain. This review aims to offer a critical perspective on current research and propose future directions for leveraging miRNA-based interventions in the fight against PC.